ANTESEDEN DARI CONTINUANCE INTENTION TO USE E-PAYMENT DANA PADA PENGGUNA GENERASI Z - Harisma, Ainun; Padmalia, Metta (Parsimonia - Jurnal Ekonomi dan Bisnis, 2023)
The development of the Internet is increasing day by day, and more companies are trying to create products and services to meet people's needs. So the company must continue to work to create a strategy that attracts consumers. This study aims to determine sales promotion, perceived ease of use of DANA e-payment with customers as an Intervening Variable in Generation Z. The population in this study are active users of DANA e-payment for transactions. The number of samples used as many as 120 respondents through purposive sampling with data collection (questionnaire). The media analysis used in this research is the SmartPLS program. The results showed that Sales Promotion had a significant positive effect on Customer Satisfaction, Perceived ease of use had a significant positive effect on customer satisfaction, Customer satisfaction had a significant positive effect on Continuance Intention to Use, Sales Promotion had a significant positive effect on Continuance Intention to use through Customer Satisfaction as an Intervening Variable, and Perceived Ease of Use has a significant positive effect on Continuance Intention to Use through Customer Satisfaction as an Intervening Variable.